PELAYANAN IBADAH UMRAH TERHADAP JEMAAH LANJUT USIA PT. CAHAYA MADINAH MANDIRI CABANG SIWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The journal created aims to describe how PT. Cahaya Madinah Mandiri Siwa Branch provides Umrah services to elderly pilgrims. With two sub-problems, namely: 1) What are the steps for the Umrah service for the elderly congregation of PT. Cahaya Madinah Mandiri Siwa Branch? and 2) What are the obstacles in the Umrah service for PT's elderly congregation, Cahaya Madinah Mandiri Siwa Branch? The research objectives are to find out and describe: 1) Umrah services for elderly congregations of PT. Cahaya Madinah Mandiri Siwa Branch 2) Obstacles in Umrah services for elderly pilgrims, PT. Cahaya Madinah Mandiri Siwa Branch. This type of research is qualitative research with a scientific approach in the field of Hajj and Umrah management as well as a service strategy approach. Research location: PT. Cahaya Madinah Mandiri Siwa Branch. The primary data source in this research was obtained from interviews with the main director, general administration division, financial administration division, and elderly Umrah pilgrims at PT. Cahaya Madinah Mandiri Siwa Branch. Secondary data sources include photos, archives, literature, and data from the PT. Madinah Mandiri Siwa Branch. The data collection methods are observation, interviews, and documentation methods. Analysis of research data by data reduction, data presentation, and drawing conclusions. The results of this research indicate that the form of Umrah service for elderly pilgrims at PT. Cahaya Madinah Mandiri Siwa Branch is a special service that serves elderly pilgrims according to their needs by adopting a responsible attitude and prioritizing the comfort and safety of elderly congregations. Services provided by PT. Cahaya Madinah Mandiri Siwa Branch start before departure and continue with services upon arrival in Saudi Arabia. PT. Cahaya Madinah Mandiri Siwa Branch ensures that the congregation carries out the Umrah pilgrimage in accordance with Islamic law so that a memorable trip is created. Even though they still encounter several obstacles in serving elderly pilgrims, they can still be resolved with the best solution according to the conditions and needs of the elderly congregation. The implications of this research for PT. Cahaya Madinah Mandiri Siwa Branch continue to strive to provide the best service according to the needs of the elderly congregation so that the congregation can feel satisfied with the services provided by PT. Cahaya Madinah Mandiri Siwa Branch.